STRATEGI GURU DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA MASA PANDEMI COVID 19 - Siti Aisyah (Pendidikan Agama Islam Institut Agama Islam Diniyyah Pekanbaru, 2021)
This journal aims to find out strategies by all teachers, especially Islamic religious education teachers during the covid 19 pandemic. This pandemic makes all aspects of the impact that are very extraordinary, all sectors experience shocks, especially in the education sector. The education sector has to change learning strategies that are different from before, usually done face-to-face, now it is distance learning or the consequences are having to change all learning from lesson planning to evaluation. In the study of the learning strategies used by teachers in learning Islamic religious education, the first three stages of planning, planning the learning media, planning applications that will be used for learning and planning the implementation of learning to evaluation. The second strategy in this activity the teacher implements the strategy starting with pre-learning activities carried out in the form of question and answer interactions, information exchange or reciprocal relationships between teachers and students with a one-way or two-way pattern. The three evaluations during this pandemic are forms of evaluation that can be done in this bold learning, namely in the form of a choice test filled out by students through a google form and presenting tasks that must be done by students.